1997
DOI: 10.1016/s0925-4773(96)00629-6
|View full text |Cite
|
Sign up to set email alerts
|

The C-terminal domain of Mad-like signal transducers is sufficient for biological activity in the Xenopus embryo and transcriptional activation

Abstract: We report the characterization of two vertebrate homologs of Drosophila mothers against dpp (Mad) isolated from the mouse and the Xenopus embryo, named MusMLP (mad-like protein) and XenMLP, respectively, together with a summary of their expression patterns in the embryo. Overexpression of XenMLP causes ventralization of Xenopus embryos and we demonstrate that the C-terminal domain is necessary and sufficient to confer this biological effect. This domain also has the potential for transcriptional activation, as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
37
0

Year Published

1997
1997
2003
2003

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(40 citation statements)
references
References 63 publications
3
37
0
Order By: Relevance
“…Mink lung epithelial cells (Mv1Lu) transfected with GST-tagged SmSmad2 showed some nuclear fluorescence with most of the fluorescence localized in the cytoplasm. This observation is similar to the results of previous studies on Smad3 (48) and Xenopus Mad-like protein (XenMLP) (49). Treatment of transfected Mv1Lu cells with rhTGF-␤ 1 resulted in predominant nuclear localization of SmSmad2, demonstrating that SmSmad2 responded to the signals initiated by the human ligand.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Mink lung epithelial cells (Mv1Lu) transfected with GST-tagged SmSmad2 showed some nuclear fluorescence with most of the fluorescence localized in the cytoplasm. This observation is similar to the results of previous studies on Smad3 (48) and Xenopus Mad-like protein (XenMLP) (49). Treatment of transfected Mv1Lu cells with rhTGF-␤ 1 resulted in predominant nuclear localization of SmSmad2, demonstrating that SmSmad2 responded to the signals initiated by the human ligand.…”
Section: Discussionsupporting
confidence: 89%
“…Consistent with this observation, Liu et al (20) and Hayashi et al (51) reported that full-length Smad1 and Smad2 and Smad1 C-terminal domain could function as agonist-dependent and agonist-independent transcriptional activators, respectively, when fused to the DNA-binding domain of GAL4. Other studies also indicate that the transactivation function may not be dependent on the ability of the protein to be phosphorylated (49).…”
mentioning
confidence: 99%
“…Fusing Smad7 with a heterologous DNA-binding domain revealed that the Smad7 MH2 domain has a potential transcriptional activation domain (data not shown), although less efficient than that of the MH2 domains of Smad1 and Smad4 (21,22). The N-terminal region of Smad7 shows little similarity to MH1 domains, which are capable of binding DNA directly.…”
Section: Discussionmentioning
confidence: 98%
“…Smad proteins share two regions of high sequence similarity, termed Mad homology (MH) 1 and MH2 domains, at the N-and C-terminal regions, respectively. The N-terminal domain has been shown to have direct sequencespecific DNA-binding activity (17)(18)(19)(20), and the C-terminal domain can act as a transcriptional activator (21,22).…”
mentioning
confidence: 99%
“…Smad proteins share two regions of high similarity, termed MH1 and MH2 domains, connected with a variable proline-rich sequence (18,19). The C-terminal part of Smad2 when fused to a heterologous DNA-binding domain, was found to have transcriptional activity (20,21), whereas the intact Smad2 protein fused to a DNA-binding domain was latent, but transcriptional activity was unmasked after stimulation with ligand (20).…”
mentioning
confidence: 99%